Patient and clinician-reported experiences of using electronic patient reported outcome measures (ePROMs) as part of routine cancer care - Amelia Payne; Ashley Horne; Neil Bayman; Fiona Blackhall; Layla Bostock; Clara Chan; Joanna Coote; Marie Eaton; Jacqueline Fenemore; Fabio Gomes; Emma Halkyard; Margaret Harris; et al. (SpringerOpen, 2023)
Abstract Background Cancer and its treatment can have significant impacts on health status, quality of life and functioning of patients. Direct information from patients regarding these aspects can be collected via electronic platforms in the form of electronic Patient Reported Outcome Measures (ePROMs). Research has shown that the use of ePROMS in cancer care leads to improved communication, better symptom control, prolonged survival and a reduction in hospital admissions and emergency department attendance. Acceptability and feasibility of routine ePROM collection has been reported by both patients and clinicians but to date their use has predominantly been limited to clinical trials. MyChristie-MyHealth is an initiative from a UK comprehensive cancer centre The Christie NHS Foundation Trust which incorporates the regular collection of ePROMs into routine cancer care. This study, carried out as part of a service evaluation, explores patient and clinician experiences of using the MyChristie-MyHealth ePROMs service. Results 100 patients with lung and head and neck cancers completed a Patient Reported Experience questionnaire. All patients reported that MyChristie-MyHealth was easy to understand and, almost all found it timely to complete and easy to follow. Most patients (82%) reported it improved their communication with their oncology team and helped them to feel more involved with their care (88%). A large proportion of clinicians (8/11) felt ePROMs helped communication with their patients and over half (6/10) felt they led to consultations being more patient focused. Clinicians also felt that the use of ePROMs resulted in patients being more engaged in consultations (7/11) and their cancer care in general (5/11). Five clinicians reported that the use of ePROMs altered their clinical decision making. Conclusions Regular ePROMs collection as part of routine cancer care is acceptable to both patients and clinicians. Both patients and clinicians feel their use improved communication and increased the feeling of patient involvement with their care. Further work is needed to explore the experiences of patients that did not complete the ePROMs as part of the initiative and to continue to optimize the service for both patients and clinicians.